Modeling UPFC into multi-machine power systems - Hassan, L.H.; Moghavvemi, M.; Almurib, H.A.F. (King Fahd University of Petroleum and Minerals., 2012)
Modeling of unified power flow control (UPFC) into multi-machine power systems by Wang, published by IET, has been widely quoted by many researchers. However, the correctness of the derivation of its equations has not been strictly scrutinized. The model cannot properly represent power system networks in its current form and need to be corrected. In this paper, the model proposed by Wang is revisited and the equations re-derived obtaining different results. The corrected model was developed and tested on three-machine and New England power systems installed with a UPFC. The DC link capacitor voltage is controlled in UPFC by modulating the phase angle of the excitation transformer voltage. The effect of the controller in damping of the low-frequency oscillations is demonstrated by using the proposed correct model and the results are compared with model presented by Wang.